2003
DOI: 10.1084/jem.20021337
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Antitumor Immunity in Mice Deficient in CD69

Abstract: We investigated the in vivo role of CD69 by analyzing the susceptibility of CD69−/− mice to tumors. CD69−/− mice challenged with MHC class I− tumors (RMA-S and RM-1) showed greatly reduced tumor growth and prolonged survival compared with wild-type (WT) mice. The enhanced anti–tumor response was NK cell and T lymphocyte–mediated, and was due, at least in part, to an increase in local lymphocytes. Resistance of CD69−/− mice to MHC class I− tumor growth was also associated with increased production of the chemok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
158
1
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(177 citation statements)
references
References 52 publications
(79 reference statements)
15
158
1
3
Order By: Relevance
“…A positive correlation between the expression of CXCR4 and CD69 on CD4 T cells and CD8 T cells derived from chronically inflamed liver samples was recently reported [7]. Interestingly, it has recently been shown that CD69 positively regulates TGF-g secretion [40]. This finding may indicate that the CD69/TGF-g / CXCR4 pathway is involved in the retention of recently activated lymphocytes in the liver.…”
Section: Discussionmentioning
confidence: 53%
“…A positive correlation between the expression of CXCR4 and CD69 on CD4 T cells and CD8 T cells derived from chronically inflamed liver samples was recently reported [7]. Interestingly, it has recently been shown that CD69 positively regulates TGF-g secretion [40]. This finding may indicate that the CD69/TGF-g / CXCR4 pathway is involved in the retention of recently activated lymphocytes in the liver.…”
Section: Discussionmentioning
confidence: 53%
“…This suggests that the immunosuppressive effects of FTY720 on collagen-induced arthritis are a result of its antagonistic effects, although it does not exclude possible agonistic effects of FTY720 on endothelial cells for immunosuppression. CD69 expression is induced after activation of mature lymphocytes at inflammatory sites (48)(49)(50)(51)(52)(53) and is required for the production of the anti-inflammatory cytokine, TGF-b, from lymphocytes (54). Furthermore, an exacerbation of collageninduced arthritis due to defective TGF-b production from lymphocytes in the synovium was observed in CD69-deficient mice (55).…”
Section: Discussionmentioning
confidence: 99%
“…Murine mAb CD69 2.2 (IgG1-j), specific for mouse CD69, was generated as described [9,17,18]. mAb 2.2 was purified from concentrated supernatants obtained in an INTEGRA CL 350 flask (Integra Biosciences AG, Switzerland) using a protein G column (Pharmacia-Biotech, Uppsala, Sweden).…”
Section: Antibodiesmentioning
confidence: 99%
“…In CD69-deficient (CD69 -/-) mouse hematopoietic cell development, thymocyte positive and negative selection and T cell maturation are normal under physiological conditions [8]. Tumor challenge of CD69 -/-mice showed that NK cell-dependent tumor rejection is enhanced in the absence of CD69 [9]. Moreover, CD69 -/-mice, when challenged with antigen, also developed an exacerbated form of collagen-induced arthritis (CIA) [10].…”
Section: Introductionmentioning
confidence: 99%